Budaya Hukum Keluarga di Indonesia: Suatu Pendekatan Futuristik - Anggi Windiarty; Surya Sukti; Mustar Mustar (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2026)
This article aims to analyze the legal culture of family law in Indonesia using a futuristic approach. The study examines the characteristics of family legal culture within the context of legal pluralism, the influence of social and technological changes on its transformation, and its future projections. This research employs a normative legal method with statutory, conceptual, case, comparative, and historical approaches. The findings indicate that family legal culture in Indonesia is pluralistic, shaped by state law, religious law, and customary law. Technological advancements and globalization have influenced family relations, increased legal awareness, and introduced new digital-based legal practices. In the future, family legal culture is projected to evolve toward a more adaptive, digital, and human rights-oriented system while still maintaining local and religious values. Therefore, harmonization among legal systems and a responsive approach to social dynamics are necessary to ensure the relevance and effectiveness of family law.